The Conscience of the Party: Hu Yaobang, China’s Communist Reformer: by Robert L. Suettinger - Messingschlager, Stefan (Journal of the European Association for Chinese Studies, 2025)
The Conscience of the Party: Hu Yaobang, China’s Communist Reformer By Robert L. Suettinger Cambridge, Massachusetts & London: Harvard University Press, 2024. 488 pp. ISBN: 9780674272804